Pathological roles of the VEGF/SphK pathway in Niemann-Pick type C neurons - Lee, Hyun; Lee, Jong Kil; Park, Min Hee; Hong, Yu Ri; Marti, Hugo; Kim, Hyongbum; Okada, Yohei; Otsu, Makoto; Seo, Eul-Ju; Park, Jae-Hyung; Bae, Jae-Hoon; Okino, Nozomu; et al. (Nature Communications, 2014)
Sphingosine is a major storage compound in Niemann-Pick type C disease (NP-C), although the pathological role(s) of this accumulation have not been fully characterized. Here we found that sphingosine kinase (SphK) activity is reduced in NP-C patient fibroblasts and NP-C mouse Purkinje neurons (PNs) due to defective vascular endothelial growth factor (VEGF) levels. Sphingosine accumulation due to inactivation of VEGF/SphK pathway led to PNs loss via inhibition of autophagosome-lysosome fusion in NP-C mice. VEGF activates SphK by binding to VEGFR2, resulting in decreased sphingosine storage as well as improved PNs survival and clinical outcomes in NP-C cells and mice. We also show that induced pluripotent stem cell (iPSC)-derived human NP-C neurons are generated and the abnormalities caused by VEGF/SphK inactivity in these cells are corrected by replenishment of VEGF. Overall, these results reveal a pathogenic mechanism in NP-C neurons where defective SphK activity is due to impaired VEGF levels.
Gesehen am 11.12.2020